Institutional challenges for flexible pricing policy: the case of Kuala Lumpur - Masram, Haidaliza (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
center. A flexible pricing policy was implemented to encourage the private sector to build more houses within the urban areas for the lower income group. This paper will look at the institutional framework of low cost housing delivery system in Malaysia in implementing the policy with Kuala Lumpur as the case study. The institutional framework is assessed through two aspects: 1). A content analysis of the institutions’ roles, responsibilities and scope of work and 2) The planning approval process at the local government level. This is then validated by a semi-structured interview to further establish the parameters. The paper is however limited to identification of institutional parameters for the development of an institutional framework in implementing the flexible policy model. The findings suggested that the institutional framework does not complement the implementation of the policy. There are loopholes in implementing the policy comprehensively. Identification of the institutional parameter is important to contribute towards the development of a new institutional framework.